Successful Retention of Postpartum Genital Prolapse with Buhner’s Suture in Three Jaffarabadi Buffaloes – A Case Study - Parmar, Kirankumar; Vadher, Dhruv; Solanki, Jayesh; Patel, Meet; Devmurari, Yash; Pranami , Ruchir (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The eversion of genital organs or their prolapse is a  condition mostly seen during or within a few hours  after postpartum in cows and buffaloes. Genital prolapse  is the dislodgment of intra-pelvic structures like the vagina,  uterus, and bladder from the normal anatomical position  through the vaginal opening. It is regarded as an emergency  condition and should be managed before excessive edema,  mucosal trauma, contamination, and fatal haemorrhage  lead to a grave prognosis (Miesner and Anderson, 2008). This  communication reports successful management of uterine  prolapse in three Jaffarabadi buffaloes using Buhner᾽s suture  as a retention technique.
Keywords: pluriparous; Jaffarabadi; prolapsed; haemorrhage; temperature